Proses Tradisi Ngorek dalam Upacara Nyongkolan pada Masyarakat Sasak Desa Tanak Awu Kecamatan Pujut Kabupaten Lombok Tengah - Masyhuri; Nursapti; Suud; Akbar, Ahmad Naufal (IAIN Madura, 2024)
This study aims to: determine the process of the Ngorek tradition in the Nyongkolan ceremony in the Sasak community of Tanak Awu Village, Pujut District, Central Lombok. This study uses a qualitative approach with an ethnographic method. The data was used with primary data sources and secondary data with data sources of research subjects and informants. Data collection in this study used interview, observation and documentation techniques. Meanwhile, data analysis uses analysis techniques developed by Miles and Hubermen with the stages of data reduction, data presentation and drawing conclusions. The results of the study revealed that (1) the implementation of the ngorek tradition is carried out in three stages, namely the preparation stage, preparing the tools and materials for the ngorek tradition for the Nyongkolan Ceremony in the Sasak Community of Tanak Awu Village, such as traditional keris clothing and sengkebal oil. The ngorek tradition is carried out at the Nyongkolan event in the Sasak Community of Tanak Awu Village by stabbing oneself or other ngorek with sharp weapons on the body and other body parts. and (3) the closing of the nyongkolan tradition, the Nyongkolan Ceremony in the Sasak Community of Tanak Awu Village, which ends with the nyongkolan and pengorek participants disbanding.